A clinical case. Tuberculous lymphadenitis in a 10-year-old girl: what should not be forgotten - Alfiya I. Aminova; Larisa I. Feldfiks; Aliya I. Ibatullina; Tatiana Yu. Eryushova; Nigar N. Muradova; Anna D. Kondrashova; Ilona A. Shcherbanyuk; Aysun A. Khalilova; Anna V. Chukanova (LLC "MEDIAFORMAT", 2023)
Tuberculosis is an infectious disease, with many forms and localizations, caused by Mycobacterium tuberculosis, which can affect any organs and tissues of the body. The paper presents a clinical case of tuberculosis of multiple locations, with the presence of resistance of M. tuberculosis to anti-tuberculosis drugs (moxifloxacin, amikacin, bedaquiline), manifesting with sluggish lymphadenopathy of the submandibular lymph nodes in a child who arrived in russia from Pakistan.